Command in War - Van Creveld M.; Van Cleveld Martin (Cambridge London Harvard University Press, 1985)
In the first book to deal specifically with the nature of command, Martin van Creveld traces the development of command from ancient Greece to Vietnam, treating historically the variety of problems involved in decision making, communication, weaponry, and logistics. The book demonstrates how command has worked in key battles - including Napolean's victory at Jena, Moltke's Koniggratz campaign, the 1973 Arab-Israeli war, and U.S. actions in Vietnam - and discusses the search for certainty in command - certainty about the intentions of the enemy, the environment of battle, and the character of one's own forces.
Keywords: 32